Pemanfaatan Limbah Organik Rumah Tangga Untuk Pembuatan Eco-Enzyme - Bertha Iin Esti Indraswanti; Sunoto; Muhammad Ridwan (Kreativasi : Journal of Community Empowerment, 2022)
The COVID-19 pandemic has changed many people's lifestyles. Restrictions on community activities require the community to be smart in dealing with the situation to be able to maintain economic conditions and the health of their families. In the development of society which is now instantaneous, the increase in public consumption is also followed by an increase in waste which is a source of environmental problems (pollution). With the majority of the livelihoods of the residents of Beringin Raya Village being informal, they are most affected by the pandemic. Therefore, there needs to be other activities that provide direct benefits to the community. An activity that is easy to do and provides great benefits, one of which is to process organic household waste for something more valuable, in this case eco enzyme. With housewives as the spearhead of change, their involvement in outreach activities to increase knowledge and skills is important. Not only the provision of materials but also demonstrations of making eco-enzymes and distribution of samples became the motivation to make changes.